Ultrasonic velocity measurements of hydration numbers of sugars in alcohol-water solutions - JUSZKIEWICZ, Adam (Archives of Acoustics, 1981)
This paper describes a method for finding the hydration numbers of electrolytes and non-electrolytes based on ultrasound velocity measurements in a mixed ethanol-water solvent. The hydration numbers of sugars such as: glucose, mannose, arabinose, xylose, saccharose and lactose were determined. Interpretation of the results obtained on the basis of the theory of "specific hydration" for sugars was presented.